1994
DOI: 10.1128/iai.62.1.60-64.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that L-(+)-lactate dehydrogenase deficiency is lethal in Streptococcus mutans

Abstract: In order to construct an effector strain for the replacement therapy of dental caries, we wished to combine the properties of low-level acid production and high-level colonization potential in a strain of Streptococcus mutans. To this end, we made a deletion in the lactate dehydrogenase (LDH) gene cloned from the bacteriocin-producing S. mutans strain JH1000. However, we were unable to substitute the mutant for the wild-type allele by transformation with linear DNA fragments. The mutated gene, carried on a sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…are: Fru, fructose; Gal, galactose; LDH, lactate dehydrogenase; PFL, pyruvate-formiate lyase; Pi, inorganic orthophosphate; PK, pyruvate kinase. et al, 1987;Hillman et al, 1994;de Soet et al, 2000;Takahashi-Abbe et al, 2003). These extracellular compounds being the responsible of acidic activity ascribed to S. mutans (Takahashi et al, 1991;de Soet et al, 2000;Takahashi and Nyvad, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…are: Fru, fructose; Gal, galactose; LDH, lactate dehydrogenase; PFL, pyruvate-formiate lyase; Pi, inorganic orthophosphate; PK, pyruvate kinase. et al, 1987;Hillman et al, 1994;de Soet et al, 2000;Takahashi-Abbe et al, 2003). These extracellular compounds being the responsible of acidic activity ascribed to S. mutans (Takahashi et al, 1991;de Soet et al, 2000;Takahashi and Nyvad, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Through BLAST, we found that HM9 ( l ‐lactate dehydrogenase) is highly conserved among different bacterial species. Research has mainly focused on the functions of this enzyme (Hillman et al., 1994; Wyckoff et al., 1997), and it was reported that l ‐lactate dehydrogenase was identified as one of the predominant immunogenic proteins in pigs naturally or experimentally infected with Mycoplasma hyopneumoniae (Frey et al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its pathogenicity, lactate dehydrogenase (LDH) deficiency can be used as the approach for reducing acidogenicity in the construction of the BCS3-L1 strain. 70 Cloning the structural gene encoding the S. mutans LDH provided the basis for producing LDH-deficient clones, 71,72 suggesting that LDH-deficiency was a lethal mutation in most S. mutans strains. However, at high sugar concentrations, the levels of activity of these enzymes are ap-parently insufficient to compensate for the absence of LDH.…”
Section: Replacement Therapymentioning
confidence: 99%